2005
DOI: 10.1152/ajpheart.00584.2004
|View full text |Cite
|
Sign up to set email alerts
|

Normal distribution of ventricular pressure-volume area of arrhythmic beats under atrial fibrillation in canine heart

Abstract: We previously found the frequency distribution of the left ventricular (LV) effective afterload elastance (E(a)) of arrhythmic beats to be nonnormal or non-Gaussian in contrast to the normal distribution of the LV end-systolic elastance (E(max)) in canine in situ LVs during electrically induced atrial fibrillation (AF). These two mechanical variables determine the total mechanical energy [systolic pressure-volume area (PVA)] generated by LV contraction when the LV end-diastolic volume is given on a per-beat ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(34 citation statements)
references
References 21 publications
(56 reference statements)
2
32
0
Order By: Relevance
“…EW), EDV, and ESP also fluctuated simultaneously. As for these fluctuations under AF, we have already analyzed them in detail [4,5,8,[12][13][14][15]. Figure 2 plots LV EW (open circles) and its efficiency (solid circles) against the predicted LV VO 2 of arrhythmic beats for 30 s in one canine heart.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…EW), EDV, and ESP also fluctuated simultaneously. As for these fluctuations under AF, we have already analyzed them in detail [4,5,8,[12][13][14][15]. Figure 2 plots LV EW (open circles) and its efficiency (solid circles) against the predicted LV VO 2 of arrhythmic beats for 30 s in one canine heart.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Suprathreshold electrical stimulation at 20 Hz via these electrodes induced and maintained AF [1,[3][4][5][6], which started on and stopped off the stimulation. We produced AF for 2 min and recorded LVP and LVV during the latter 1 min at sampling intervals of 3 ms with a computer.…”
Section: Surgical Preparationmentioning
confidence: 99%
“…In these studies, we have found the positive correlation between E max and the preceding beat interval [5]; the apparently nonnormal or non-Gaussian frequency distributions of the beat interval, heart rate, and effective arterial elastance (E a ) [1,2]; and the normal or Gaussian distributions of the end-systolic pressure-volume (P-V) ratio or maximal elastance (E max ) as a load-independent contractility index and the systolic P-V area (PVA) as a measure of the LV total mechanical energy [3,7]. As for the E max , E a , and PVA [7][8][9][10][11][12], see the LV P-V diagram schematically shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations